Multimodal Interactive Flipbook Arias Model-Based for Critical Thinking Skills - Arie Anang Setyo; Muhammad Ruslan Layn; Ba’diana Adil Lestari (EduMa: Mathematics education learning and teaching, 2024)
Multimodal interactive flipbook is a digital-based learning aid which utilizes technological advances with learning materials presented in the text, images, audio, video, website, and web-based or interactive. Thus, this study aims to examine the effectiveness of multimodal interactive flipbooks based on the ARIAS (Assurance, Relevance, Interest, Assessment, Satisfaction) to improve students' critical thinking skills. This development study uses ADDIE model (Analysis, Design, Development, Implementation, Evaluation). It focuses on the Implementation and Evaluation stages to measure the effectiveness of the developed product in improving critical thinking skills. The data collection used a learning outcome test oriented critical thinking skill, then analyzed using descriptive and N-gain statistics. The results show that the interactive flipbook based on the ARIAS learning model is effectively implemented to improve the critical thinking skills of the mathematics education study program students of Universitas Muhammadiyah Sorong, who are significantly less critical to critical